(untitled) (Bangladesh Pharmaceutical Journal, 2022)
Leaves of Bruguiera gymnorhiza (L.) Lam. are very popular traditional remedies used by tribal people of Bangladesh near to Sundarbans. The purpose of this work was to assess the pharmacological attributes of methanolic extract of leaves of B. gymnorrhiza employing mice model. Using the well-known tail tipping method, the in vivo glucose-lowering ability of methanolic extract of leaves of B. gymnorrhiza was investigated. The writhing experiment was performed to determine peripheral analgesic activity. The anti-diarrheal activity was determined utilizing the castor oil-induced diarrhea in the mice model. In consequence, oral treatment of the extract at 400 mg/kg b.w. dose caused significant suppression of acetic acid-induced writhing (58.33%). The findings were comparable to the corresponding standard diclofenac (50 mg/kg b.w.) that exhibited 86.67% inhibition of abdominal writhing. Besides, after 180 min of oral ingestion (400 mg/kg) of the extract, the maximum reduction in blood glucose (38.46%) was found, compared to standard glibenclamide (73.67%). Furthermore, when compared to conventional loperamide (65.06%), there was a 40.02% reduction in diarrheal feces at 400 mg/kg b.w. dose. The methanolic extract of leaves of B. gymnorrhiza has strong peripheral analgesic and anti-diarrheal efficacy, as well as modest glucose-lowering effect, according to these in vivo bioassays. Further studies are still recommended to isolate bioactive molecules in order to develop novel drug moieties. Bangladesh Pharmaceutical Journal 25(1): 26-31, 2022 (January)